THE POTENTIAL OF GINGEROL ACTIVE COMPOUNDS IN ZINGIBER OFFICINALE AS ANTI-CANCER AGENTS - Kamalia Layal; Aisyah Anggun H; Nadya Salsabillah; Syarinta Adenina (International Journal of Islamic and Complementary Medicine, 2024)
Cancer is a type of chronic disease which is the main cause of death in the world with 19.3 million new cases in 2020. Current cancer treatment includes surgery, chemotherapy, radiotherapy, hormone therapy, antiangiogenesis inhibitors, stem cell therapy, and others. Long-term cancer treatment can cause other health problems, so alternative anti-cancer therapy with the fewest side effects is needed. One natural ingredient that is known to prevent and act as anti-cancer therapy is Zingiber officinale. Zingiber officinale contains gingerol which functions as an anti-oxidant, anti-inflammatory, anti-bacterial, anti-cancer, anti-tumor and anti-mutagenic. The anticancer effects of gingerol are known to be effective in cancers of the liver, stomach, mouth, prostate, breast and ovaries. This literature aims to delve deeper into the role of gingerol as an anti-cancer compound. The strategy employed in the article search involved using electronic databases such as Google Scholar and PubMed. Keywords utilized included "cancer," "red ginger," "gingerol," "Zingiber officinale," and "anticancer." The articles selected were those published within the last 10 years. The study results indicate that gingerol is beneficial in oral, breast, lung, colorectal, cervical, and prostate cancers. The mechanism of action of gingerol involves pathways such as the PI3K/AKT, JAK/STAT, apoptosis, and ROS proliferation pathways. Gingerol is known to be effective as an anti-cancer agent and has the potential to become one of the alternative anti-cancer treatments.